Hydraulic turbine start-up: a fluid-structure simulation methodology. Issue 2 (March 2019) - Melot, Matthieu; Coulaud, Maxime; Chamberland-Lauzon, Joël; Nennemann, Bernd; Deschênes, Claire
Abstract: In the present work, a one-way fluid-structure coupling approach is proposed with a focus on the fluid modelling. Main engineering quantities are compared against the thorough laboratory measurements coming from the BulbT project which is led by the Consortium on Hydraulic Machines and the LAMH (Hydraulic Machine Laboratory of Laval University). Good agreement is obtained with main engineering quantities as well as pressure sensors and strain gauges on the runner blades. Moreover, pressure sensor signals on the runner blades and the hydraulic computations results allow to give a description of the flow topology in the runner during the start-up and speed-no-load operating points.